2020
DOI: 10.1101/2020.06.03.131672
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rab2 drives axonal transport of dense core vesicles and lysosomal organelles

Abstract: Long range fast axonal transport of neuropeptide-containing dense core vesicles (DCVs), endolysosomal organelles and presynaptic components is critical for maintaining the functionality of neurons. How the transport of DCVs is orchestrated remains an important unresolved question.The small GTPase Rab2 has previously been shown to mediate DCV biogenesis and endosomelysosome fusion. Here we use the Drosophila model system to demonstrate that Rab2 also plays a critical role in bidirectional axonal transport of DC… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 76 publications
(117 reference statements)
1
6
0
Order By: Relevance
“…A recent study shows that regulators of axonal transport of these different cargos are distinct. Loss of the small GTPase Rab2 in Drosophila disrupts axonal transport of DCVs and endo‐lysosomes without altering mitochondrial trafficking 72 . Alternatively, increasing evidence suggests that the endoplasmic reticulum (ER) plays a critical role in the regulation of endo‐lysosomal size and positioning, 73–76 and disruption of ER dynamics could potentially specifically disrupt endo‐lysosomes.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study shows that regulators of axonal transport of these different cargos are distinct. Loss of the small GTPase Rab2 in Drosophila disrupts axonal transport of DCVs and endo‐lysosomes without altering mitochondrial trafficking 72 . Alternatively, increasing evidence suggests that the endoplasmic reticulum (ER) plays a critical role in the regulation of endo‐lysosomal size and positioning, 73–76 and disruption of ER dynamics could potentially specifically disrupt endo‐lysosomes.…”
Section: Discussionmentioning
confidence: 99%
“…This phase is characterized by cargo exchange between endo-lysosomal compartments and immature vesicles budding off from the trans-Golgi network (Topalidou et al, 2016). Recent studies (Gondré-Lewis et al, 2012; Lund, Lycas, Schack, Andersen, & Gether, 2020) suggest that RAB2 and associated proteins are involved in this exchange. However, we do not know if these components participate in routing DILPs and AKH to DCVs in the CC.…”
Section: Discussionmentioning
confidence: 99%
“…Since lysosomes are essential for maintaining synapses (Farfel-Becker et al, 2019;Goo et al, 2017;Lund et al, 2021;Padamsey et al, 2017) and we found that lysosomes are dysfunctional in aged neurons, we decided to investigate if lysosomal dysfunction caused synapse loss in aged neurons.…”
Section: Lysosome Dysfunction Contributes To the Aging-dependent Loss...mentioning
confidence: 99%